(untitled) (Sains Humanika, 2019)
ISO 9000 is a quality management system widely used. ISO 9000 has begun being implemented in Malaysia’s IPT since the 1990s as one of the initiatives for quality assurance. While the number of HEIs in Malaysia that are implementing ISO 9000 is increasing, however, empirical studies of the implementation of the system are still underdeveloped. Therefore, the objective of this article is to study the implementation steps of ISO 9000 quality management system at Malaysian HEI. This study uses a qualitative approach by using case study as a research strategy. A public HEI located in Selangor was chosen as a research location. This study uses a semi-structured interview method carried out on fifteen informants who are actively involved in the implementation of ISO 9000. The informants represent the categories of faculty management, quality coordinator and lecturers. The data were analyzed using thematic analysis method which was assisted by Nvivo software. The research finding show that the implementation of ISO 9000 in the HEI involves seven steps; organizational context analysis, training, leadership, development of work groups, implementation, monitoring and improvement. All these steps have been well implemented with participation from all faculty members. The results of this study contribute to the development of knowledge related to the implementation of ISO 9000: 2015 in Malaysian HEI.Â The research findings can be employed as a guideline to university administrators, public sector officers or corporate managers in their effort to implement ISO 9000 effectively in their respective organizations.